BACTERIOLOGICAL AND CLINICAL PROFILES CORRELATED WITH ANTIBIOTIC RESISTANCE IN PATIENTS WITH ACUTE ATTACKS OF COPD - Mandozai Imaad Gulam Ahmed Khan (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
ABSTRACT: Background: In Chronic Obstructive Pulmonary Diseases (COPD), recurrent acute attacks are common and presumed to occur due to repeated bacterial infections. There is a correlation between the acute attacks of COPD and acquiring antibiotic resistance or infection with newer strains of organisms. The present study, a prospective, clinical correlative one was undertaken to isolate the organisms, to know their sensitivity and antibiotic resistance.Aim of the study:  To study and isolate the organism in the sputum of patients admitted with acute attacks of COPD and to correlate their resistance to newer antibiotics with the presenting clinical features.Materials: 67 consecutive patients diagnosed with acute attacks of COPD attending the Department of General Medicine, Medicover Hospitals, Hyderabad, Telangana were considered for the study. Demographic details, spirometry values as per GOLD 2018 guidelines, antibiograms of the sputum samples were correlated with clinical severity and analyzed and compared with other studies in the literature.Results: The study of 67 patients included 46 (68.65%) males and 21 (31.34%) females with a male-to-female ratio of 2.19:1. The mean age was 58.25±4.85 years. Patients aged between 45 and 65 years were 50 (74.62%) of the total 67 patients. A history of smoking was present in 44 (65.67%) patients with a smoking index of 224.7 ± 98.32. P. aerugenes (31.34%) was the most commonly isolated and cultured bacteria, followed by Klebsiella Pneumoniae (22.38%), S. Pneumoniae (09.12%), and H. influenzae (08.46%). P. aeruginosa was also the most resistant to Cefoperazone-sulbactam (29%). This was followed by Ciprofloxacin (28%). K. Pneumoniae was the most resistant to Cefoperazone-sulbactam in 63% of the isolates and levofloxacin in 39% of the isolates. S. Pneumoniae was the most resistant to Ciprofloxacin in 41% of the isolates, and Amoxicillin-clavulanic acid in 36%.Conclusions: Bacteriological Profile in patients with acute attacks of COPD has a significant bearing upon the severity of the disease and its recurrence.  The commonest bacteria encountered in the bacterial isolates were P. Aeruginosa and K. Pneumoniae. There was a significant correlation between the bacteriological profile of the sputum samples and their impact on the acute attacks of AECOPD. The study highlighted the differences in bacteriological profile in comparison to other studies. P. Aerugnes was the most common bacteria isolated and confirmed its role in acute attacks of severe degree AECOPD. The prevalence of antibiotic resistance to common bacteria suggested that the severity of the acute attacks of COPD could be attributed to the existence of antibiotic-resistant strains.  The susceptibility of both Gram-positive and Gram Negative bacteriae to broad spectrum Carbapenems was higher when compared to Ceftriaxone and Cefaperazone+sulbactum.